Immunopathological mechanisms involved in SARS-CoV-2 infection - Sávio Breno P. Brito; Isaque O. Braga; Marília M. Moraes; Carolina C. Cunha; Sydney C. Leão; Iukary Takenami (Sociedade Brasileira de Patologia Clínica, 2020)
ABSTRACT Introduction: Coronavirus disease 2019 (Covid-19) has become a global health emergency. Although many scientific advances have been achieved over the last few months, the knowledge about how the etiologic agent SARS-CoV-2 interacts with the host's immune system, regulating the pathogenesis and the outcome of the disease, is not yet fully understood. Objective: This is a narrative literature review to discuss the available evidence on modes of transmission and the main immunopathological mechanisms involved in SARS-CoV-2 infection. Material and method: A search in the indexed journals was carried out in the PubMed/MEDLINE database, during the period from January to May 2020. The following descriptors were used in the research: Covid-19, SARS-CoV-2, transmission, immunity, immunopathogenesis, and pathogenesis. Results and discussion: Transmission of SARS-CoV-2 occurs through contact with airway secretions from a symptomatic patient. However, scientific evidence encourages transmission by asymptomatic and/or oligosymptomatic patients. Immunopathological studies suggest that the hypercytokinaemia promotes lung tissue damage and, subsequently, organ and system involvement, leading to decompensation, organ dysfunction and death. Regarding the humoral response, the high titers of B lymphocytes and antibodies, traditionally, correlated with the protection of the host, may be associated with the severity of the disease by SARS-CoV-2. Conclusion: The host's immune response is determinant in the pathogenesis of Covid-19. However, further in vivo and/or in vitro studies are needed to elucidate the pathogenic mechanisms of SARS-CoV-2 and, thus, assist in the development of a vaccine and/or therapeutic target.